Inovasi E-Modul Berbasis Literasi Sains Dan Numerasi - Nyamik, Nyamik Rahayu Sesanti; Sesanti, Nyamik Rahayu; Wahyuningtyas, Dyah Tri (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2022)
Application and development of teaching materials need to be done in today's learning innovations. Currently the government is implementing a new curriculum with new policies in the form of learning numeracy and scientific literacy. This learning focuses on daily problem-solving activities related to science and mathematics. Therefore there is a need for teacher innovation in developing E-Module teaching materials as a form of modern learning application. The development of E-Module learning was carried out at SD IT Insan Mulia with 10 teachers participating. This was done because teachers at SD IT Insan Mulia did not understand how to make E-Modules based on scientific literacy and numeracy. The method used is the Scientist-Practitioner Model, which combines training, workshops and mentoring. The results obtained in this activity were that several teachers stated that they already knew and understood how to make E-Modules based on scientific literacy and numeracy in accordance with what had been taught. In addition, teachers are also given assignments in groups to apply what has been taught how to make E-Modules based on scientific literacy and numeracy. Based on this, the teacher produces good products so that learning can take place practically anywhere and anytime through the E-Modules that have been made